Florida CItrus Activity Book - Jamie D. Burrow; Megan M. Dewdney; Michael E. Rogers; Timothy M. Spann; Tripti Vashisth (EDIS)
The Florida Citrus Activity Book is a basic introduction to Florida citrus trees, diseases, and pests. This book is for elementary students.